2020
DOI: 10.3892/etm.2020.8783
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity on the prognosis of hypertensive disorders in pregnancy

Abstract: The prevalence of pathologies due to placental dysfun ction superimposed on pregnancy is constantly increasing. The prognosis of the cases complicated by gestational hypertension is usually good, significantly better compared with that of the cases associating preeclampsia. About half of the cases with gestational hypertension will progress to preeclampsia, the risk of decompensation being inversely proportional to the gestational age of the onset of gestational hypertension. The present study, analyzed the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
(15 reference statements)
1
12
0
1
Order By: Relevance
“…In a previous study, we found obesity and underlying cardiac pathology to be significant risk factors for severe preeclampsia (30). In the present study we confirmed that there was a significant difference in the presence of complications such as IUGR, oligohydramnios, prematurity, fetal arrhythmia, acute fetal distress, HELLP syndrome, and placental abruption for group 5 patients with severe preeclampsia, compared with the group with pregnancy-induced hypertension (Table II).…”
Section: Resultssupporting
confidence: 86%
“…In a previous study, we found obesity and underlying cardiac pathology to be significant risk factors for severe preeclampsia (30). In the present study we confirmed that there was a significant difference in the presence of complications such as IUGR, oligohydramnios, prematurity, fetal arrhythmia, acute fetal distress, HELLP syndrome, and placental abruption for group 5 patients with severe preeclampsia, compared with the group with pregnancy-induced hypertension (Table II).…”
Section: Resultssupporting
confidence: 86%
“…By comparing the ROC curve areas, lactate proved to be superior to pH in predicting poor neonatal outcome. In addition, although there are numerous proposals for cutoff values of pH and lactate to be used for confirming IA and predicting a poor outcome (23,24), the greatest sensitivity and specificity were achieved in our study by using a cutoff value of 7.24 for pH and 3.75 mmol/l for lactate (Table II).…”
Section: Resultsmentioning
confidence: 68%
“…Various risk factors for HTLV-1 infection have been reported in pregnant women or in women of reproductive age which include: increasing age, young age at first sexual intercourse, history of abortion and history of transfusion, history of sexually transmitted infections, multiparity, low income, low educational level, high number of sexual partners, and relatives with history of leukaemia/lymphoma. Considering that the HTLV-I carrier mothers generally detected belong to a low socio-economic class, it should be interesting to study the role of malnutrition in susceptibility to infection, take into account the magnitude of hypovitaminosis and the impact of it on immunological system, especially in low income class and endemic areas (15)(16)(17)(18)(19). Anyway, we did not find any risk factor in our case, the age of the mother being under 40, and healthy supplemented nutrition proving ineffective in prevention of viral load increase.…”
Section: Discussionmentioning
confidence: 99%